José Bergamín A Critical Introduction, 1920-1936 - Dennis, Nigel (Heritage, 1986)
Writer, critic, and cultural activist José Bergamín (1895-1983) was unjustly relegated to the sidelines of contemporary Spanish intellectual life for reasons that have more to do with his political dissidence and long periods of exile than with the interest and importance of his written work. This book represents the first attempt to come to terms with that work. Professor Dennis's study focuses on the period 1920-1936, the so-called silver age of Spanish literature, during which Bergamín rose to prominence alongside a group of superlatively gifted writers and friends, among them Frederico Garcia Lorca, Rafael Alberti, Jorge Guillén, and Pedro Salinas. It sets out to explain the nature of the relationship Bergamín had as a critic and prose writer with the major poets of the 1920s and 1930s, and at the same time systematically examines the singularity of his own work as an aphorist, essayist, and dramatist. Professor Dennis also devotes attention to explaining the sense of Bergamín's initiative in founding the important journal Cruz y Raya (1933-1936) and the role this publication played, both culturally and politically, during the troubled years of the Second Republic. This book not only fills a notable gap in our understanding of pre--Civil War literary and intellectual life in Spain, but also lays the foundation for all future research into the work of this fascinating and enigmatic writer